Does panpsychism entail anti-realism? The worm in the panpsychist apple - Albahari, Miri (Religious studies, 2026)
Panpsychists commonly hang onto the ‘realist’ assumption that our world with its structures has an observer-independent, often spatial element to it, even while they claim that those structures are realized by the experiences of subjects. I argue that this assumption is the ‘worm in the apple’ that lurks behind two of panpsychism’s major problems: the subject (de)combination problem and what I call the ‘inner-outer gap problem’. Abandoning this assumption sidesteps those problems, but commits panpsychism to anti-realism.